Constrained choices? Linking employees' and spouses' work time to health behaviors. (February 2015) - Fan, Wen; Lam, Jack; Moen, Phyllis; Kelly, Erin; King, Rosalind; McHale, Susan
Abstract: There are extensive literatures on work conditions and health and on family contexts and health, but less research asking how a spouse or partners' work conditions may affect health behaviors. Drawing on the constrained choices framework, we theorized health behaviors as a product of one's own time and spouses' work time as well as gender expectations. We examined fast food consumption and exercise behaviors using survey data from 429 employees in an Information Technology (IT) division of a U.S. Fortune 500 firm and from their spouses. We found fast food consumption is affected by men's work hours—both male employees' own work hours and the hours worked by husbands of women respondents—in a nonlinear way. The groups most likely to eat fast food are men working 50 h/week and women whose husbands work 45–50 h/week. Second, exercise is better explained if work time is conceptualized at the couple, rather than individual, level. In particular, neo-traditional arrangements (where husbands work longer than their wives) constrain women's ability to engage in exercise but increase odds of men exercising. Women in couples where both partners are working long hours have the highest odds of exercise. In addition, women working long hours with high schedule control are more apt to exercise and men working long hours whose wives have high schedule flexibility are as well. Our findings suggest different health behaviors may have distinct antecedents but gendered work-family expectations shape time allocations in ways that promote men's and constrain women's health behaviors. They also suggest the need to expand the constrained choices framework to recognize that long hours may encourage exercise if both partners are looking to sustain long work hours and that work resources, specifically schedule control, of one partner may expand the choices of the other. Highlights: Fast food consumption is affected by men's work hours in a nonlinear way. Neo-traditional arrangements promote men's but constrain women's ability to engage in exercise. Different health behaviors may have distinct antecedents. Schedule control of one partner expands the choices of the other, but in a gendered way.